The new valence state [Ga]−5 in Li-Ga-Te system under high pressure. (October 2021) - Li, Yixuan; Tian, Fubo; Zhou, Qingyan; Yang, Mengxin; Wang, Youchun; Shi, Changmin; Wang, Xiaoli
Abstract: The density-functional theory is used to search for the candidate structures of Li-Ga-Te system below 100 GPa. Several new stable structures are uncovered, namely, P -3 m 1 LiGaTe2, P 4/ mmm Li9 GaTe2, Immm Li9 GaTe2 . The band-gap of the I -42 d LiGaTe2 and P 4/ mmm Li9 GaTe2 corresponds to the peak position of the imaginary part of the dielectric function. Meanwhile, a new chemical valence of Ga atom under high pressure with [Ga] −5 ionic charge state is found. The dense accumulation of Li atoms and high pressure caused the change of valence state of Ga. Highlights: Several new stable structures are uncovered, namely, P -3 m 1 LiGaTe2,   P 4/ mmm  Li9 GaTe2,   Immm  Li9 GaTe2 . The band-gap of  I -42 d  LiGaTe2  and  P 4/ mmm  Li9 GaTe2  corresponds to the peak position of imaginary part of dielectric function. A new chemical valence of Ga atom under high pressure with [Ga] -5  ionic charge state is found.